OS PROGRAMAS DE FORMAÇÃO CONTINUADA DE PROFESSORES DA EDUCAÇÃO INFANTIL DA REDE MUNICIPAL DE CAMPO GRANDE E O TRABALHO DE MEDIAÇÃO DO COORDENADOR PEDAGÓGICO. - MARIANA SAYD BELLÉ (2023)
This dissertation is linked to line of research 1: History, Policies and Education of the postgraduate program in education at UFMS (PPGEdu/UFMS). The research intends to analyze the continuing teachers education programs implemented by the Municipal Education System of Campo Grande, within the scope of Early Childhood Education, therefore examines the attributions of the Pedagogical Coordinator in this formative process. In the conformation of the research field of this work, the themes of public policies, teacher education and teaching work are interconnected in a way that it would not be possible to carry out the proposed reflections without entering into these studies. With the determination of the presence of the pedagogical coordinator in all institutions of early childhood education in the city of Campo Grande as one of the strategies of the Municipal Education Plan - (2015 - 2025), it becomes relevant to examine the ways of its performance in the organization of the pedagogical work and subsidizing the teacher's work. In this way, the laws, national policies and internal regulations formulated by the Municipal Department of Education of Campo Grande to subsidize the process of continuing education of teachers were analyzed and the way that the role of the coordinator is presented in these documents. For that, a bibliographic review was carried out about the conceptions of social and educational policies and documental analysis, with reference to authors such as Brzezinski (2018), Dourado (2007), Gatti (2009), Libâneo (2016), Pacheco (2013, 2016), and Shiroma & Cunha (2016). Furthermore, questionnaires and interviews with pedagogical coordination professionals in early childhood education institutions were applied with the purpose of identifying the strategies and actions implemented by the pedagogical coordinators directed at the effectiveness of the process of continuing education of the teaching workforce. By using theoretical-methodological references of dialectical historical materialism, three categories of analysis were defined: contradiction, work and mediation. Such categories were articulated in an attempt to understand the relationships and implications of capital forces on educational policies, teaching work and the coordinator's mediation. In this analysis, some authors who supported the reflections stands out, such as Derisso (2013), Mészáros (2011, 2006), Martins (2010), Paro (2006, 2010, 2016), Russo (2007) and Saviani (2017). The research showed that the national policies of continuing education for early childhood education instituted in recent years prioritize the transmission of methodologies and training of teachers with a focus on the performance of external evaluations. Likewise, the training programs offered by the municipal system approach specific and urgent training needs, without linking the formative work of the coordinator with the department´s actions with little to no connection with the daily challenges of each institution. In this way, the coordinator's work possibilities in the teacher training process becomes underused when they are attached to the determinations and guidelines of training programs. On the other hand, by assuming the role of mediator in the teacher education process, the coordinator has the ability to act in the transformation of the educational process and to assist in effective emancipatory human formation. Keywords: Teaching policies. Continuing formation. Pedagogical coordination. Early childhood education. Teaching work.